A review of emerging IL-17 inhibitors in the treatment of psoriasis focusing on preclinical through phase II studies. (1st November 2016) - Campa, Molly; Menter, Alan
ABSTRACT: Introduction: Interleukin-17 has recently been identified as a key player in the pathogenesis of psoriasis. As such, several drugs targeting IL-17 are in various stages of clinical development. Areas c overed: In this review, the authors describe several emerging therapies and drug candidates targeting IL-17. The authors detail many biologic injectable drug candidates as well as numerous potential oral and topical small molecule drug candidates. Expert o pinion: Approval of IL-17 inhibitors has significantly improved the treatment options for psoriasis patients. Secukinumab and ixekizumab are approved in both Europe and the USA, and brodalumab is likely facing approval by the end of 2016. Numerous additional biologic and small molecule drug candidates are in the pipeline, and once deemed safe and effective will likely offer significant benefit to our psoriasis population.